Digital minigame as a food and nutritional education tool for adolescents (Revista Contexto & Saúde, 2025)
The objective of this study was to develop a digital minigame to promote adequate, healthy and sustainable eating among adolescents. The educational game was planned and developed in mobile (Android) and desktop (website) versions by an expert team, based on the Brazilian Dietary Guidelines. The Unity platform was used for its creation and the following tools, C#, spriter, gimp and photoshop, for animation, movement, scoring and art. After developing of the game, it will be validated by an expert panel and later will be used in a pilot study with adolescents. It is concluded that “FeiraNutre” minigame is an educational tool capable of transforming the teaching-learning process into an engaging, interactive and fun experience. The playful strategy use can help the player relate the game content to his eating habits, so that they can then present healthier and more sustainable food choices. This possibility has contributed to games being continually introduced in technical schools and with the advantage of being used in face-to-face, remote, hybrid and distance learning.
Keywords: Game; Food and nutritional education; Adolescent